2021
DOI: 10.1159/000518945
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease Patients’ Perspectives during COVID-19 Pandemic: Results from a Portuguese Survey

Abstract: <b><i>Introduction:</i></b> Patients with inflammatory bowel disease (IBD) do not seem to be at increased risk of infection by SARS-CoV-2, but there is a concern whether immunosuppressive therapy may be associated with more severe disease. Several clinical practice recommendations have been published to help guide IBD care during the COVID-19 pandemic. Nonetheless, few studies have addressed patients’ perspectives and fears. We aimed to evaluate Portuguese IBD patients’ perspectives on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, a Portuguese survey recorded how patients believed they were at an increased risk of severe COVID-19 if they had active IBD or were taking corticosteroids within three months[ 22 ]. In addition, Pellegrino et al [ 23 ] reported a reduction in therapeutic adherence during outpatient follow-up during the COVID-19 pandemic at a referral IBD centre in southern Italy by employing a remote questionnaire-based interview.…”
Section: Telemedicine: General Considerationsmentioning
confidence: 99%
“…For example, a Portuguese survey recorded how patients believed they were at an increased risk of severe COVID-19 if they had active IBD or were taking corticosteroids within three months[ 22 ]. In addition, Pellegrino et al [ 23 ] reported a reduction in therapeutic adherence during outpatient follow-up during the COVID-19 pandemic at a referral IBD centre in southern Italy by employing a remote questionnaire-based interview.…”
Section: Telemedicine: General Considerationsmentioning
confidence: 99%